2017
DOI: 10.1242/jcs.199570
|View full text |Cite
|
Sign up to set email alerts
|

Cellular functions of WASP family proteins at a glance

Abstract: Proteins of the Wiskott–Aldrich syndrome protein (WASP) family function as nucleation-promoting factors for the ubiquitously expressed Arp2/3 complex, which drives the generation of branched actin filaments. Arp2/3-generated actin regulates diverse cellular processes, including the formation of lamellipodia and filopodia, endocytosis and/or phagocytosis at the plasma membrane, and the generation of cargo-laden vesicles from organelles including the Golgi, endoplasmic reticulum (ER) and the endo-lysosomal netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
172
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(181 citation statements)
references
References 86 publications
1
172
0
Order By: Relevance
“…Because WASp and WAVE proteins are integral signaling activators of the Arp2/3 complex (15), we hypothesized that LAT-independent SLP-76 microclusters associated with WASp and WAVE. Using TIRF microscopy, we found that GML did not affect the association between phosphorylated SLP-76 microclusters and phosphorylated WASp microclusters in activated T cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because WASp and WAVE proteins are integral signaling activators of the Arp2/3 complex (15), we hypothesized that LAT-independent SLP-76 microclusters associated with WASp and WAVE. Using TIRF microscopy, we found that GML did not affect the association between phosphorylated SLP-76 microclusters and phosphorylated WASp microclusters in activated T cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This lower potency likely stems from a fewer (than in formins and Ena/VASP) number of G-actin binding domains and, possibly, a less favorable geometry for oligomer binding to NPFs. Of note, depending on the involvement in a particular cellular process (i.e., remodeling of cytoplasmic [31], endosomal [32], autophagosomal [33, 34], Golgi and ER membranes [35, 36], or contribution to cytoplasmic streaming [37], etc. ), the Arp2/3 complex can be activated by different NPFs, of which only two were tested in the present study: VCA fragment of N-WASP in the in vitro assays (Figures 2G–O) and WAVE in the cellular context (Figures 2D–F).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, JMY, an NPF that regulates transcription in the nucleus and vesicle trafficking between the ER and trans -Golgi network [38-40], with its three WH2-domains, is likely to be inhibited more efficiently than N-WASP and WHAMM (each containing two WH2-domains), which regulate endocytosis [41] and autophagosome formation [33], respectively. Furthermore, all these NPFs are likely to be more efficiently inhibited than single WH2-domain NPFs WASP, WAVE, and WASH, which are involved in endocytosis, cell migration and endosomal trafficking (recently reviewed in [31]). Notably, inhibition of many of these processes would be beneficial for pathogenic bacteria to interrupt migration, phagocytosis, and activation of immune cells, disrupt epithelial contacts, inhibit Golgi-dependent maturation of granules in immune effector cells and their release, and inhibit autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Wash encodes several biochemical activities, including actin nucleation and actin/MT binding, bundling, and crosslinking (Liu et al, 2009;Verboon et al, 2018;Verboon et al, 2015a); however, when working in concert with the SHRC, Wash often functions upstream of the Arp2/3 complex to promote branched actin filament formation (cf. (Alekhina et al, 2017;Rottner et al, 2010). Mounting evidence has also demonstrated roles for actin and Arp2/3 complexes in diverse nuclear functions (Alekhina et al, 2017;Kyheroinen and Vartiainen, 2019;Percipalle and Vartiainen, 2019).…”
Section: The Arp2/3 Complex Is Required For Ne-buddingmentioning
confidence: 99%